The Effect of Positive Thinking Skills and Innovative Behaviour on Performance and its Impact on Employee Loyalty - Susanto, Xena Monica (Fakultas Bisnis, 2024)
Companies face many challenges, including retaining, adapting and growing the capabilities of innovative and positive employees. In addition, companies also need to have the ability to engage with employees in their work effectively. The purpose of this study examines how the variables of positive thinking skills and innovative behavior affect employee performance and its impact on employee loyalty. This research explores how the development of positive thinking skills influences the emergence of innovative behaviour and thus affects overall performance outcomes and the cascading impact of these variables on employee loyalty, emphasising the importance of a positive mindset and innovative approach in shaping organisational dynamics. The research findings offer valuable insights for organisations aiming to increase employee engagement and loyalty by strategically addressing positive thinking skills and encouraging a culture of innovation, thus providing a comprehensive understanding of the crucial role these factors play in shaping employee loyalty.This research was conducted using the Structural Equation Modeling method with the help of Smart PLS Software. Hair method was used to determine the sample size, and 154 respondents were generated. The results showed that positive thinking ability and innovative behavior affect employee performance directly, innovative behavior affects employee loyalty directly, and performance as an intervening variable affects employee loyalty indirectly. The implication for the company is that if the company wants to improve employee performance, the company needs to improve positive thinking ability and innovative behavior, while if the company wants to improve employee loyalty, the company needs to improve innovative behavior and positive thinking ability through improved employee performance.